Disturbances of protein c activity in abdominal sepsis: Diagnostic and predictive importance - Karamarković Aleksandar P.; Mirković Darko; Stanković Nebojša; Nikolić Valentina; Jeremić Vasilije; Radenković Dejan; Stefanović Branislav (Vojnosanitetski Pregled)
Background. Despite improved diagnostic modalities, potent antibiotics, modern intensive care, and aggressive surgical treatment, more than one third of patients still die of severe secondary peritonitis. Clinical difficulties in the treatment of abdominal sepsis were related to inherent problems of limited clinical signs and the rapid spread of infection. An inflammatory process is often well under way before the presence of clinical signs and symptoms of sepsis. The aim of this prospective study was to assess diagnostic and prognostic significance of protein C in abdominal sepsis. Methods. Twenty-two patients with severe intraabdominal infections with sepsis syndrome were treated surgically as compared to 15 patients with hernia repair (control group). During the study, the following parameters were analyzed daily: protein C, AT III, plasminogen, alfa-2 antiplasmin, HMWK, C5a and C5-B9 complement, C1-inhibitor, CRP. Results. The mean APACHE II score was 17 points, with actual mortality rate of 23%. Each parameter evaluated in the abdominal sepsis group differed from the one evaluated in the control group to a great extent (p=0.001). The results and multivariate regression statystical analysis confirmed the following parameters as sensitive biological markers of septic cascade (p£0.0001-0.026): protein C, AT III, HMWK, C1-inhibitor and C5-B9 complement. According to the results the low level of protein C consistently correlated with disease severity and suggested the development of septic shock and poor outcome. Conclusion. Early diagnosis of plasma proteolytic disturbances was very important, from the diagnostic and predictive point of view, in abdominal sepsis. According to the results protein C was the most significant marker of sepsis and early predictor of the outcome of septic complications during severe intraabdominal infections (r=0.761; p=0.0001).